Context aware reliable sensor selection in IoT. (2019) - Babu, K.R. Remesh; Prathap, M. Vishnu; Samuel, Philip
Internet of things (IoT) is a computing concept where physical objects with embedded sensors connect to the internet and can identify themselves to other devices. Today, the number of devices connected to the internet is increasing rapidly and they want to communicate each other for different purposes. The future internet will comprise of billions of intelligent communicating objects having capabilities for sensing, actuating and data processing. Each object in this cyber physical systems (CPS) will have one or more embedded sensors that will capture huge amount of data. Managing these data in cloud and obtaining the relevant data from appropriate sensors are important concerns. For information retrieval context awareness is important. Usually users need information from these sensors depending upon several factors such as location, accuracy level, etc. The proposed method senses reliable data from a sensor environment that satisfies user contexts. It also contains different functionalities such as user addition, location sensing, context specification, user context counting and selection of current best results.